The properties of fly ash based geopolymer mortars made with dune sand. (15th February 2016) - Chuah, S.; Duan, W.H.; Pan, Z.; Hunter, E.; Korayem, A.H.; Zhao, X.L.; Collins, F.; Sanjayan, J.G.
Abstract: This paper reports the properties of fly ash based geopolymer mortars made with dune sand. The geopolymer mortars of different cation type, namely sodium based (Na), potassium based (K) and a mixed Na/K, were prepared with dune sand (DS) and river sand (RS). The corresponding geopolymer pastes were also prepared. A series of tests including compressive strength, modulus of elasticity, splitting tensile strength, microanalysis (using scanning electron microscopy), porosity (using mercury intrusion porosimetry), sorptivity and air void (using section analysis method) were carried out. The results showed a strong correlation between strength and porosity of geopolymeric materials. The addition of DS had influences on the chemical compositions and physical properties of geopolymer mortars. These influences were dependent on the type of cation. Based on the results of mechanical properties, DS can be utilised as the fine aggregate for the production of geopolymer based construction material. Graphical abstract: Highlights: Mechanical properties of dune sand and river sand geopolymer mortar are comparable. The geopolymer gel around dune sand surfaces morphologically resembles the bulk gel. Empirical formula for elastic modulus changes as strength of mortars is increased. The cation type affects properties of geopolymer mortars. The strength of geopolymeric materials is governed by the H2 O/Al2 O3 ratio.